Paul and Economics : A Handbook - Pickett, Raymond; Blanton, Thomas R., 1968- (Book collections on Project MUSE., 2017)
In Paul and Economics, leading scholars address a variety of topics in contemporary discussion, including an overview of the Roman economy; the economic profile of Paul and of his communities, and stratification within them; architectural considerations regarding where they met; food and drink; idol meat and the Lord's Supper; material conditions of urban poverty; patronage; slavery; travel; gender and status; the collection for Jerusalem; and the role of Marxist theory and the question of political economy in Paul scholarship.